Reform of the Criminal Law System in Indonesia Which Prioritizes Substantive Justice - Nurcahyo, Nanang; Ricky, Ricky; Laksito, FX. Hastowo Broto; Manitra , Ramalina Ranaivo Mikea (CV. Ius et Ambientis, 2024)
Indonesia is presently undergoing a reform of its criminal law system to decolonize the existing criminal legislation that persists. The existing criminal law, which the Netherlands has influenced, currently emphasizes corporal punishment and does not offer avenues for crime victims to seek compensation. However, efforts are underway to reform the criminal code and introduce provisions that allow compensation to be awarded to victims of criminal offenses. This is undertaken within the framework of Indonesia's endeavor to establish a criminal justice system that is compassionate and capable of achieving meaningful principles of fairness